Golkar Party's Political Communication Strategy in Winning the 2024 Garut Regency DPRD Legislative Elections - Putra Kurniawan, Benaldi Ramadhan; Iis Zulfah Adnan; Yandi Hermawandi (Jurnal Spektrum Komunikasi, 2024)
The purpose of this study is to see (1) how the Golkar Party's political communication strategy is to maintain its victory in the 2024 Garut Regency DPRD legislative election (2) what obstacles the Golkar Party faces in facing the 2024 Garut Regency DPRD legislative election (3) what solutions the Golkar Party has implemented in facing obstacles in the 2024 Garut Regency legislative election. The type of research used is qualitative with observation, interview and documentation methods. The results of this study indicate that (1) the Golkar Party's political communication strategy in winning the 2024 Garut Regency legislative election is to optimize all of the political party's own communication strategies, such as strengthening and selectively selecting a communicator, creating integrated and collaborative communication messages with all teams of each candidate for the council, having various communication media such as approaching community leaders to optimizing online media, and efficiency of audiences/communicants (2) the obstacles faced by the Golkar Party in maintaining its election victory are the industrialization of the party which presents new political parties to the limited freedom of civil servants to speak (3) the solution sought by the Golkar Party in facing obstacles is to continue to strengthen the party coalition and optimize communication media as a real manifestation of adding to the party's vote bank.